2016
DOI: 10.1161/circulationaha.115.019987
|View full text |Cite
|
Sign up to set email alerts
|

Relative Risk Factors for Cardiac Erosion Following Transcatheter Closure of Atrial Septal Defects

Abstract: Background-Transcatheter closure of secundum atrial septal defects (ASD) using the Amplatzer septal occluder is generally safe and effective, but erosion into the pericardial space or aorta has been described. Although the absolute risk of this complication is low, there has been no assessment of relative risk factors. Methods and Results-All erosions reported to St. Jude Medical after ASD closure with an Amplatzer septal occluder (cases) were compared with controls (matched 2:1) who underwent ASD closure but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
112
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 24 publications
0
112
0
3
Order By: Relevance
“…This can only be accomplished by identifying subgroup(s) of patients with a significantly higher risk of erosion than the overall population risk. To date, the single consistent risk factor for device erosion is deficient retro-aortic rim(10,38). However, deficient retro-aortic rim is extremely prevalent in pediatric patients (between 40–60%)(30,3941), and it is not clear that the current definition of deficient retro-aortic rim discriminates the patients at highest risk of device erosion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can only be accomplished by identifying subgroup(s) of patients with a significantly higher risk of erosion than the overall population risk. To date, the single consistent risk factor for device erosion is deficient retro-aortic rim(10,38). However, deficient retro-aortic rim is extremely prevalent in pediatric patients (between 40–60%)(30,3941), and it is not clear that the current definition of deficient retro-aortic rim discriminates the patients at highest risk of device erosion.…”
Section: Discussionmentioning
confidence: 99%
“…However, deficient retro-aortic rim is extremely prevalent in pediatric patients (between 40–60%)(30,3941), and it is not clear that the current definition of deficient retro-aortic rim discriminates the patients at highest risk of device erosion. There is recent evidence that patients with larger defects relative to body size and septal length and oversizing the device to the defect are more prevalent in erosions than in matched-controls(38). However, we must acknowledge that we have not yet been able to define a strata of patients in whom O-ASD is clearly favorable in terms of risk to TC-ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the complications from erosion occur within 1 year of device closure, but more than 10% of the cases of erosion occurred more than 1 year after device closure [4]. With proper clinical follow-up, early erosion can be treated appropriately [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, O ’Byrne et al [5] have argued that it is not associated with an increased risk of technical failure or early adverse events. On the other hand, McElhinney et al [4] have evaluated the relative risk factors and revealed that deficiency of any rim, the ratio of the size of the device to the size of the rim, and oversized devices are associated with erosion. A recent study has shown that absence of the aortic rim, poor posterior rim consistency, septal malalignment, and dynamic morphology of the ASD in echocardiographic findings can significantly increase the risk of erosion [6].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients diagnosed with late erosion after implant are significantly older than those presenting earlier. 3 The reasons are not fully clear, but different tissue properties may have a potential role. As in our patient an ASD occluder was implanted in childhood and no signs of erosion were present at serial echoes, we can assume that further factors other than age at implant can contribute to the timing of onset of the erosion.…”
Section: Case Reportmentioning
confidence: 99%